The effects of cattle on the development of plant communities in rehabilitating coastal dune forests at Richards Bay, KwaZulu-Natal, South Africa - Van Aarde, Rudi J. (University of Pretoria, 2022)
Dissertation (MSc (Zoology))--University of Pretoria, 1998.